2009
DOI: 10.1097/inf.0b013e3181aa6b2d
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Serum Antibodies Reactive With Enterohemorrhagic Escherichia coli Virulence-Associated Factors by Healthy Brazilian Children and Adults

Abstract: Our results demonstrate an increasing anti-LPS and antiprotein antibody response with age, which could provide protection against EHEC infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
1
5
0
1
Order By: Relevance
“…In line with another previous study performed with the same neonate/mother population (Palmeira et al, 2009), the present work demonstrated high anti-lipopolysaccharide O111 IgM levels in maternal sera from all three groups (except when compared with anti-O6 lipopolysaccharide IgM levels). These findings suggest that these high levels are due to a previous high prevalence of this serogroup in past decades, representing the enteropathogenic E. coli (EPEC) group considered to be the leading causes of diarrhea in infants in many developing countries, including Brazil (Nataro & Kaper, 1998), as well as a reflection of the more recent high prevalence of the Shiga toxin-producing E. coli (STEC) strains group.…”
Section: Discussionsupporting
confidence: 92%
“…In line with another previous study performed with the same neonate/mother population (Palmeira et al, 2009), the present work demonstrated high anti-lipopolysaccharide O111 IgM levels in maternal sera from all three groups (except when compared with anti-O6 lipopolysaccharide IgM levels). These findings suggest that these high levels are due to a previous high prevalence of this serogroup in past decades, representing the enteropathogenic E. coli (EPEC) group considered to be the leading causes of diarrhea in infants in many developing countries, including Brazil (Nataro & Kaper, 1998), as well as a reflection of the more recent high prevalence of the Shiga toxin-producing E. coli (STEC) strains group.…”
Section: Discussionsupporting
confidence: 92%
“…Pro tective immunity to intimin, the product of the eae gene, is acquired in early childhood, which might explain why adults are less affected by infections with classical LEEpositive EHEC and enteropathogenic E. coli strains (14,30,36,64,79,80). Some LEE-negative STEC strains have other colonization mechanisms that might be more relevant in patients of various age groups (82,83,103,104).…”
Section: Natural Reservoir For Eahec O104:h4 Is Humans In Contrast Tomentioning
confidence: 96%
“…However, the data obtained in this study cannot support the notion that these transferred Stx2 antibodies afford protection to children. A relatively high frequency of serum samples of healthy adults living in São Paulo City showed neutralizing activity against Stx2, as demonstrated by Vero cell culture assays [23]. We tested the serum of two HUS patients and two controls, but did not detect neutralizing activity in HUS serum, although a partial neutralization was observed in one control serum (data not shown).…”
Section: Discussionmentioning
confidence: 95%
“…Palmeira et al [23] investigated the ability of sera obtained from healthy adults to neutralize Stx2. Thus, seroepidemiological data regarding anti-Stx2 antibodies in the Brazilian population and the use of serodiagnosis could help to explain the epidemiological profile of the illness.…”
Section: Introductionmentioning
confidence: 99%